Investigation On The Interaction Analysis Of Beam-Nonlinear Isolator With Low And High Stiffness Support - Turahim, K.K; Djidjeli, K.; Xing, J. T. (Journal of Engineering and Technology (JET), 2024)
This paper presents the study of the interaction between a beam and a nonlinear isolator for low and high supporting stiffness. The system consists of an elastic beam- like structure and a geometrically nonlinear isolation system in which a horizontal degree provides a physical approach for realising the required horizontal force. The generalised dynamic equations of the system are derived and the modal summation method is used to analyse the beam. The dynamic interaction mechanism between the nonlinear isolation system and the elastic structure is revealed. The beam- nonlinear isolator design for low stiffness support and high stiffness support is discussed. It is found that the beam provides additional mass, stiffness and force to the nonlinear vibration isolator and the requirement to perform ground vibration test whereby the rigid mode of the beam must be less than one third of the first elastic natural frequency of the free-free beam has been satisfied. The condition to achieve high stiffness support has also been satisfied. Nonlinear dynamical behaviour of the beam-nonlinear isolator indicates that period doubling bifurcation occurs when the excitation force is 1 and excitation frequency is 0.5Hz. Poincare’ maps reveals that the system form closed loops and no chaotic behaviour is observed. Perfomance analysis in terms of force transmissibility of the nonlinear isolator shows that the nonlinear isolator performs better than a linear isolator and also performs better than a hardening HSLDS mount.